Myasthenia Gravis and Physical Exercise: A Novel Paradigm - O'Connor, Laura; Westerberg, Elisabet; Punga, Anna Rostedt (Frontiers in Neurology, 2020)
The benefits of physical exercise for healthy individuals are well established, particularly in relation to reducing the risks of chronic lifestyle related diseases. Furthermore, physical exercise has been seen to provide beneficial effects in many chronic diseases such as multiple sclerosis, rheumatoid arthritis, and chronic obstructive pulmonary disease and is therefore recommended as part of the treatment regimen. Myasthenia Gravis (MG) is a chronic autoimmune disease that causes neuromuscular transmission failure resulting in abnormal fatigable skeletal muscles weakness. In spite of this fluctuating skeletal muscle weakness, it is reasonable to assume that MG patients, like healthy individuals, could benefit from some of the positive effects of physical exercise. Yet exercise-related research in the field of MG is sparse and does not provide any guidelines on how MG patients should perform physical training in order to obtain exercise’s favourable effects without risking disease deterioration or more pronounced muscle fatigue. A handful of recent studies report that MG patients with mild disease activity can adhere safely to general exercise recommendations, including resistance training and aerobic training regimens, without subjective or objective disease deterioration. These findings indicate that MG patients can indeed improve their functional muscle status as a result of aerobic and high-resistance strength training. This knowledge is important in order to establish collective as well as personalised guidelines on physical exercise for MG patients. This review discusses the present knowledge on physical exercise in MG.